Hubungan Status Gizi dengan Kejadian Menarche Siswa SDN 02 Kota Prabumulih - Suryanda Suryanda (Jurnal Vokasi Kesehatan, 2017)
Abstract: Nutritional Status Associated With Menarche On Female Students Of Public Elementary School 02 Prabumulih. The most influential factor on secondary sexual development is a hormone in which its formation influenced by good nutritional status, so it accelerates the formation of hormones that affect the arrival of menarche.The purpose of research was to determine correlation of nutritional status with the incidence of menarche on female students of public elementary school 02 Prabumulih. It was descriptive analytic research with cross-sectional method. The population in this study were female students of 4 classes V grade and 4 classes of VI grade, with totally 211 female students who attended in Public Elementary School 02 Prabumulih. This research used random sampling technique and calculation of sample size obtained by 64 female students. Data were obtained through check list questionnaire and body mass index measurement. The result were 43 people (67,2%) had menarche and 21 other had not menarche yet (32,8%), while 38 (59,4%) had normal nutritional status and 26 people (31,6%) had abnormal status were 11 people (42,3%) obese, skinny 15 people (57,7%) under weight. Statistical test using chi square with 95% confidence level (a = 0.5) indicates there was correlation between nutritional status with the incidence of menarche.Abstrak: Hubungan Status Gizi Dengan Kejadian Menarche Siswi Sdn 02 Kota Prabumulih. Faktor yang sangat berpengaruh terhadap perkembangan seksual sekunder adalah hormon dimana pembentukannya dipengaruhi oleh status gizi yang baik, sehingga dapat mempercepat pembentukan hormon-hormon yang mempengaruhi datangnya menarche. Tujuan penilitian yaitu untuk mengetahui hubungan status gizi dengan kejadian menarche siswi SDN 02 Kota Prabumulih. Penelitian ini bersifat penelitian deskriptif analitik dengan menggunakan metode cross-sectional. Populasi adalah siswi kelas V terdiri dari 4 kelas dan VI terdiri dari 4 kelas berjumlah 211 siswi yang bersekolah di SDN 02 Kota Prabumulih tahun 2016. Penelitian ini menggunakan teknik random sampling dan perhitungan besar sampel didapatkan 64 siswi. Data diperoleh melalui kuesioner berbentuk check list dan pengukuran Indeks Massa Tubuh. Didapatkan hasil 43 orang (67,2%) telah mengalami menarche dan 21 orang belum mengalami menarche ( 32,8%), sedangkan 38 (59,4%) orang status gizi normal dan 26 orang (31,6%) status gizi tidak normal, yaitu obesitas 11 orang (42,3%) sedangkan kurus 15 orang (57,7%). Uji statistik menggunakan chi square dengan tingkat kepercayaan 95 % (a=0.5) menunjukkan terdapat hubungan antara status gizi dengan kejadian menarche di SDN 02 Kota Prabumulih.Â